2018
DOI: 10.1002/ijc.31552
|View full text |Cite
|
Sign up to set email alerts
|

Risk of virus and non‐virus related malignancies following immunosuppression in a cohort of liver transplant recipients. Italy, 1985–2014

Abstract: This cohort study assessed, in Italy, the overall pattern of risk of de novo malignancies following liver transplantation (LT). The study group included 2,832 individuals who underwent LT between 1985 and 2014 in nine centers all over Italy. Person-years (PYs) at cancer risk were computed from 30 days after LT to the date of cancer diagnosis, to the date of death or to the end of follow-up. Excess cancer risk, as compared to the general population, was estimated using standardized incidence ratios (SIRs) and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…De novo malignancies (DNMs) are a leading cause of death in liver transplant (LT) recipients [1][2][3][4][5][6][7][8], and survival probability of LT recipients, who develop a DNM, is generally lower than that of nontransplanted patients with the same tumor [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…De novo malignancies (DNMs) are a leading cause of death in liver transplant (LT) recipients [1][2][3][4][5][6][7][8], and survival probability of LT recipients, who develop a DNM, is generally lower than that of nontransplanted patients with the same tumor [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐organ transplant recipients are known to be at higher risk of developing several cancer types, mainly virus‐related malignancies, compared with the general population . The large number of investigations that have explored cancer incidence in transplant recipients has not been paralleled by investigations focused on the prognostic impact of de novo malignancies (DNMs) .…”
Section: Introductionmentioning
confidence: 99%
“…Solid-organ transplant recipients are known to be at higher risk of developing several cancer types, mainly virus-related malignancies, compared with the general population. [1][2][3][4] The large number of investigations that have explored cancer incidence in transplant recipients has not been paralleled by investigations focused on the prognostic impact of de novo malignancies (DNMs). 5,6 The few studies conducted in the setting of liver transplant (LT) have suggested that the increased tumor burden among LT recipients may substantially impair their overall survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We have already published research findings showing the high risk of KS in Italian kidney and liver transplant recipients, with crude incidence rates 16-times or 6.3-times higher, respectively, than those reported by Cahoon and colleagues. 4,5 In our study, we compare time trends of KS in Italian transplant recipients with the temporal pattern described in the US by Cahoon and colleagues. To this end, using data on 11,624 recipients of kidney transplants (KTX) performed between 1997 and 2013 in 17 centers followed-up up to December 2016, we investigated trends of KS incidence highlighting the role of mTOR-inhibitors (mTORi).In a total of 85,705 person-years (PYs) of observation (median length of follow-up 7.3 years), 106 cases of KS were diagnosed, with a crude incidence rate of 123.7 KS cases/10 5 PYs, 10-times higher than the crude incidence reported in the US study conducted by Cahoon and colleagues.…”
mentioning
confidence: 99%